A new species of Danothrips from Southwestern China (Thysanoptera: Thripidae) - Li, Yajin; Xie, Yonghui; Zhang, Hongrui (Zootaxa, 2016)
Danothrips salicis sp. n. is described from young leaves of Salix sp. in Southwestern China. This species is similar to D. moundi, D. theifolii and D. trifasciatus, but can be distinguished by the colour of the fore wing, the median longitudinal split on tergite X of females, and in males by the situation of the median short thorn-like setae on tergite IX.